2011
DOI: 10.1007/s10641-011-9955-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of the ichthyoplankton in a subtropical river in Brazil

Abstract: Studies that assess reproduction dynamics and ichthyoplankton distributions are scarce for the upper Uruguay River, especially in environments such as tributary mouths. Therefore, this study aimed to evaluate: (i) ichthyoplankton composition; (ii) spatial and temporal variation in ichthyoplankton abundance; and (iii) relationships between environmental variables and the abundance of ichthyoplankton during one annual cycle in this region. Monthly samples were collected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 21 publications
3
32
0
1
Order By: Relevance
“…The proportion of individuals caught in Itá reservoir was higher than expected, and the average number of individuals was more than two times higher in Itá than in Machadinho reservoir, even standardizing fishing effort. Ichthyoplankton studies conducted in the upper Uruguay River region (Hermes-Silva et al, 2009;Reynalte-Tataje et al, 2012c) have shown that the reproductive activity of fish is much more intense in the area of Itá reservoir than of Machadinho. The scarcity of lotic environments located upstream Machadinho Dam has been credited as one of the factors that reduces reproductive activity (Hermes-Silva et al, 2009) and, consequently, interferes in the abundance of adult fish in this environment when compared with the Itá environment (Reynalte-Tataje et al, 2012c).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of individuals caught in Itá reservoir was higher than expected, and the average number of individuals was more than two times higher in Itá than in Machadinho reservoir, even standardizing fishing effort. Ichthyoplankton studies conducted in the upper Uruguay River region (Hermes-Silva et al, 2009;Reynalte-Tataje et al, 2012c) have shown that the reproductive activity of fish is much more intense in the area of Itá reservoir than of Machadinho. The scarcity of lotic environments located upstream Machadinho Dam has been credited as one of the factors that reduces reproductive activity (Hermes-Silva et al, 2009) and, consequently, interferes in the abundance of adult fish in this environment when compared with the Itá environment (Reynalte-Tataje et al, 2012c).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that environmental variables are the main determinants of ichthyoplankton abundance, structure and composition variation (Keckeis et al, 2000;Reynalte-Tataje et al, 2012). However, the effect of dams on the ichthyoplankton community is rarely investigated (Humphries & Lake, 2000;Sanches et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Turbid waters are essential for the survival of fish eggs and larvae as they decrease visual predation (Agostinho et al, 2002). In the Uruguay River basin, Reynalte-Tataje et al (2012a) reported similar results and suggested that low densities downstream of dams indicate low reproductive activity influenced by water quality and flow control, with an abundance improvement only one hundred and thirty kilometers downstream of the dam. In the Upper Parana River, this effect also seems to be minimized near the Ivinheima River, about ninety kilometers downstream of Porto Primavera, where the abundances were comparatively greater, confirming the importance of this river for this stretch of the basin.…”
Section: Discussionmentioning
confidence: 86%
“…These tributaries, in addition to maintaining the reproduction events, have still contributed with the input of larvae to the downstream stretches. Numerous studies carried out in this basin Daga et al, 2009;Gogola et al, 2010;Reynalte-Tataje et al, 2011Da Silva et al, 2015;Silva et al, 2016) and in the basins of the rivers Uruguay (Reynalte-Tataje et al, 2008, 2012aHermes-Silva et al, 2009;Corrêa et al, 2011) and São Francisco (Sato et al, 2005;Weber et al, 2013;Normando et al, 2014;Nunes et al, 2015), as well as in other parts of the world (Bottcher et al, 2013;Webber et al, 2013;López-Casas et al, 2016), have argued for the importance of free-flowing tributaries upstream of regulated rivers as alternative migratory routes. Nevertheless, it is important to emphasize the need for an adequate distance between the spawning site and the complete early embryonic and larval development, preventing the drift of larvae to inappropriate places, such as reservoirs, where they can be preyed upon or settle to the substrate Olden, 2016).…”
Section: Discussionmentioning
confidence: 99%